การใช้ยาแรนนิทิดีนในการรักษาภาวะหัวใจวายเรื้อรัง - กีรติ ฮันตระกูล (จุฬาลงกรณ์มหาวิทยาลัย, 2007)
Objectives: To determine whether the blockade of histamine H[subscript 2]-receptors using ranitidine is beneficial for the pathophysiology of chronic heart failure (CHF). Background: Because [beta][subscript 1]-adrenergic blocking agent is beneficial for the pathophysiology of CHF and activated H[subscript 2]-receptors cause activation of Gs-protein the same way as activated [beta][subscript 1]-adrenergic receptors do, so H[subscript 2]-receptor blocking agents may be beneficial for the treatment of CHF. Methods: 50 stable symptomatic CHF patients were randomly divided into 2 groups. One group received ranitidine of 300 mg/day for 16 weeks, and the other group received placebo for the same period. Blood level of NTproBNP and left ventricular function obtained by echocardiography were recorded both before and after the treatment in both groups. Results: Ranitidine of 300 mg/d increase plasma NTproBNP level (from 2,131+-3,039 pg/ml to 2,811+-4,714 pg/ml) while placebo decrease plasma NTproBNP level (from 1,710+-1,796 pg/ml to 1,485+-1,660 pg/ml) but without statistical significant (p=0.262). Conclusions: Ranitidine did not decrease NTproBNP level in patient with CHF within 16 weeks period.